Clinical implications of molecular markers in acute myeloid leukemia. (23rd October 2018) - Kayser, Sabine; Levis, Mark J.
Abstract: The recently updated World Health Organization (WHO) Classification of myeloid neoplasms and leukemia reflects the fact that research in the underlying pathogenic mechanisms of acute myeloid leukemia (AML) has led to remarkable advances in our understanding of the disease. Gene mutations now allow us to explore the enormous diversity among cytogenetically defined subsets of AML, particularly the large subset of cytogenetically normal AML. Despite the progress in unraveling the tumor genome, only a small number of recurrent mutations have been incorporated into risk‐stratification schemes and have been proven to be clinically relevant, targetable lesions. We here discuss the utility of molecular markers in AML in prognostication and treatment decision making, specifically highlighting the aberrations included in the current WHO classification.